A megtérés lélektani folyamatának pasztorálpszichológiai horizontja - Szabolcs KOVÁCS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The Pastoral-Psychological Horizon of the Conversion’s Psychological Process. The problem of the conversion requires an understandable and scientific definition for theology as well. The process of conversion, the religious attitude, the faith development are some of the processes related to the person’s intra-personal activity. Such a dynamic and complex field of research must be analysed through the perspective of several disciplines such as theological anthropology, psychological anthropology, religion-phenomenology and deep-psychology. Through these disciplines we make a deeper approach to the process of conversion and make it understandable for theology. The interdisciplinary approach has some difficulties, such as the different usage of the terminology and the borders of each fields of research. We try to bring in dialog these fields of science and get a broader access to a much debated biblical phenomena.